2014
DOI: 10.1002/ajmg.a.36414
|View full text |Cite
|
Sign up to set email alerts
|

Klippel‐Trenaunay syndromein a boy with concomitant ipsilateral overgrowth and undergrowth

Abstract: Klippel-Trenaunay syndrome comprises congenital vascular malformations of the capillary (nevus flammeus), venous (varicosities) or lymphatic systems and disturbed (usually over-) growth of one or more extremities and adjacent parts of the trunk. In some individuals the affected body area may show reduced rather than increased growth. Such patients have been described inverse Klippel-Trenaunay syndrome and included within the spectrum of the syndrome. We report on a 3-year-old boy with vascular malformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Prominent superficial veins and soft‐tissue undergrowth are also described in some CMTC patients 12 . Even though soft‐tissue and bone overgrowth is most commonly described in KTS, some cases with soft‐tissue and bony undergrowth have been reported and denominated as inverse KTS 8,11,14‐17 . Inverse KTS presents with characteristic geographic CMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent superficial veins and soft‐tissue undergrowth are also described in some CMTC patients 12 . Even though soft‐tissue and bone overgrowth is most commonly described in KTS, some cases with soft‐tissue and bony undergrowth have been reported and denominated as inverse KTS 8,11,14‐17 . Inverse KTS presents with characteristic geographic CMs.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, superficial lymphatic vesicles develop over time and venous anomalies of the involved limb become evident. However, there is considerable confusion in nomenclature and the term KTS has also been applied to patients with blotchy segmental light red to pink stains, 13,14 which would be indistinguishable from the CMs of DCMU. We prefer to restrict the term KTS to cases where there is a CM, lymphatic malformations and persistent embryologic veins or deep venous anomalies, because these patients are at risk for thrombosis or lymphedema, whereas patients with DCMO or DCMU do not seem to present with these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Sturge-Weber syndrome is caused by somatic activating mutations in the GNAQ gene, involved in intracellular signal transduction for cell proliferation [Shirley et al, 2013]. Macrodactyly has also been described in association with Klippel-Trenaunay-Weber syndrome [McGrory et al, 1991;Redondo et al, 2009;Ruggieri et al, 2014], which, in turn, has been described concomitantly with TSC in the same individual [Troost et al, 1975]. Klippel-TrenaunayWeber syndrome is characterized by the presence of localized congenital vascular malformations and disturbed growth of bone or soft tissue [Oduber et al, 2008] and its molecular etiology is still not fully understood, although somatic mosaicism for…”
Section: Discussionmentioning
confidence: 99%
“…Lower limbs are usually affected. The coincidence of upper and lower extremity involvement may occur in 10% to 15% of cases and is usually ipsilateral [206]. The VMs affect the entire limb and commonly are present from infancy.…”
Section: Klippel-trénaunay-weber Syndromementioning
confidence: 99%